BIO-EFFICACY OF CROTON BONPLANDIANUM BAILL.ON SOME WEED AND CROP PLANTS - SWAPNAL SISODIA,; G.P. SINGH, (International Journal of Pharma and Bio Sciences, 2012)
Allelo - chemicals were extracted from the leaves of Croton bonplandianumBaill.using various solvent systems. The seeds of the test plants i.e. Triticum. aestivumL.,SpinaceaoleraceaL.,Vicia sativa L.and MadicagohispidaGaertn.were treated with different extract fractions i.e. Aqueous leachates (AL), Petroleum ether Fraction (PF) Methanolic Fraction (MF) Chloroform Fraction (MF) WaterFraction (WF)} thus obtained, various germination parameters viz, percent germination, seed vigour and mean seedling growth was observed. From the results of this experiment it is explicit that the seeds of T. aestivum, S. oleracea, V. sativa M. hispida. do not germinate in an environment that possesses allelo-chemics from C. bonplandianum. This result gains support from the observation. The toxic effect of the aqueous leachates and organic extract fractions on the seeds of the test plants assumes a lot of significance since seeds is produced by the plants to ensure the perpetuation of their types and for the spread of the species to newer areas.